2017
DOI: 10.1177/0271121417715318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cloud Computing Tools to Enhance Team-Based Problem Solving for Challenging Behavior

Abstract: Multi-tiered systems of support (MTSS) provide frameworks to guide the instructional decisions and problem solving of educators (i.e., Sugai & Horner, 2009). Within MTSS, the availability of ongoing child assessment and progress monitoring data is described as a critical feature (Buzhardt et al., 2010; Sugai & Horner, 2009). For some time, there was an assumption that if tools were created to gather information about children's proficiency with and progress in developing essential learning targets, educators w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The results were consistent with Johnson's [37] study, which found that integrating cloud technology into learning helped increase the scores at a significance level of .05. Moreover, the study showed that cloud technology integration helped develop students' potential for learning and solving problems collaboratively and promoted students' higher-order thinking skills.…”
Section: Mobile Cloud-based Learning System Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…The results were consistent with Johnson's [37] study, which found that integrating cloud technology into learning helped increase the scores at a significance level of .05. Moreover, the study showed that cloud technology integration helped develop students' potential for learning and solving problems collaboratively and promoted students' higher-order thinking skills.…”
Section: Mobile Cloud-based Learning System Testingsupporting
confidence: 89%
“…Mobile learning is defined as the use of applications installed in a mobile device (tablet, smartphone, or laptop) for learning purposes in educational institutions, such as schools or universities. Mobile cloud-based learning has intriguingly facilitated the learning process, representing the mobile learning model and providing users with useful learning materials [37]. Compared with other forms of learning, learning through mobile devices is more private and has more potential for connected collaborative activities, despite being in the same learning environment [17], [19].…”
Section: Mobile Cloud-based Learningmentioning
confidence: 99%
“…Additionally, in the data-driven environment, previous rounds' learning log data empowers teachers to implement targeted interventions (Johnson, 2017).…”
Section: Peer Evaluation In Team-based Learning (Tbl)mentioning
confidence: 99%
“…Many studies in collaborative learning field have primarily focused on utilizing learner attribute data to predict performance [19], aid decision-making for incident detection [20], and to provide formative feedback through data visualization [21], [22]. For instance, the significance of domain knowledge has been emphasized in problem-solving tasks that require high knowledge construction [23], [24].…”
Section: Data-driven Support For Educationmentioning
confidence: 99%
“…When implemented in a data-driven environment, the learning log data from previous rounds empowers teachers to deliver targeted interventions [20]. With the increasing accumulation of learning log data, recent CSCL studies have opened avenues for supporting collaborative learning with state-of-the-art technical frameworks and data-rich environments [2].…”
Section: Iterative Tbl Workflow In Data-rich Environmentmentioning
confidence: 99%